Ganda mo perception of feminine beauty shaped by internal and external factors - Roy, Patricia Cristina Aporongao
"This thesis focused on how selected Filipinos perceive feminine beauty as well as its formation and the external and internal factors that influence it. Also, it focused on what feminin beauty is and the distinction of the perception of feminine beauty across gender. Review of related literature revealed that mass media and advertising equate beauty to thinness. This ideal of female beauty has a negative impact on females resulting to eating disorders and disturbance in their appearances. Furthermore, women want to improve their appearances by purchasing beauty products or resort to cosmetic surgery. It was found out too that Western ideals of beauty propagate through local television and magazine advertisements. Thus, media influences women's ideals of beauty. Also, most studies focused on certain products or campaigns when exploring about the females' perception on beauty such as skin-whitener commercials and other TV advertisements. Moreover, most studies explored the females' point of view when it comes to beauty, not exploring the perception across gender.This study adapted Firmeza's study framework (1995) and user Perception Model, Filipino Value System, Constructivism, Maslow's Hierarchy of needs, Persuasion theory, Reinforcement theory and Agenda Setting theory. Concepts from each of the theories were borrowed in order to come up with an integrated conceptual framework. The researcher conducted a series of focus interviews and focus group discussion that primarily explored into how the perception of beauty was formed and the factors that influences its formation. The focus group discussions and focus interviews gave an in depth inquiry as to what factors contributed to the meaning of beauty among selected Filipinos. Both methods employed a purposeful sampling. Findings of the study revealed that in forming perceptions of feminine beauty, a lot of factors are to be considered. External sources of information such as family, friends, partners, social groups, society & culture, work, advertisements and mass media were found out to be influential. Also, it was found out that individuals have their own standard of feminin beauty based on their upbringing and maturity. Moreover, the informants primarily associated feminine beauty with outer beauty or physical attractiveness because they shared that it is first seen by people. However, inner beauty was considered essential most expecially in interacting with other people more so, in keeping relationships with others. Inner beauty was said to be longer lasting compared to outer beauty. Furthermore, there is a need for one to be beautiful for self fulfillment and for other's acceptance. In addition, it was found out in this study that perceptions of feminine beauty vary across gender. This study will be of great use for women who have distorted perceptions of beauty and low self esteem. It will also help the audience to be more critical of what mass media present as beautiful and consider themselves as beautiful too. In addition, this study will contribute to the learning of different fields such as mass communication, arts, psychology and anthropology."